Application of the Problem-Based Learning to Improve Scientific Literacy Skills Through Practicum Worksheet for Grade 11 Students of Senior High School 1 Samalanga - Haikal Amri; Sri Setiawaty; Neli Saprina (Scientia Publica Media, 2024)
Problem-based learning (PBL) model invites students to be able and trained so that students in solving problems can improve students’ scientific literacy abilities. This research aims to determine the application of the problem basic learning (PBL) model to improve scientific literacy skills through practicum worksheet for grade XI students at Senior High School (SMA) 1 Samalanga. The subjects of this research were students in grade XI of SMA Negeri 1 Samalanga for the 2023/2024 academic year, totaling 31 students. Meanwhile, the type of research used is classroom action research. This research was conducted in two cycles. In the first cycle, the material discussed was acids and bases from various experts, and in the second cycle, the material discussed was acids and bases in daily life, including conducting practical work using worksheets. The research data collection instruments are observation, test with 5 multiple-choice questions, and questionnaires, all three of which are analyzed using a percentage test. The results of the analysis based on pretest and posttest score data using the PBL model increased from 53% to 75%. Apart from that, improvements can also be seen in the aspects of students’ attitudes and skills with an average score of 72% with “good” criteria. Based on these results, it can be concluded that the application of the problem based learning model through practicum worksheet can improve students’ scientific literacy skills. It is recommended that research using the Practicum-based PBL worksheet can be continued on other chemical materials.